The Impact of Primary and Effective Porosities on the Permeability of the Kurra Chine Formation Successions (Late Triassic) in Selected Wells - Northern Iraq - علي, محمد سليمان; الدباغ, مها منيب (Journal of Petroleum Research and Studies, 2021)
This paper highlights of calculating the permeability by using primary and secondary porosities for carbonate successions of Kurra Chine Formation in Ain Zalah-29, Butmah- 15, and Alan-1 wells. It has been based on a relatively modern method specially designed for carbonate rocks which proposed by Lucia (1995). Rather than dependence on the porosity and water saturation values in calculating permeability, this method uses the rock fabric and its relationship to the primary porosity that calculated from the sonic log. Since the sonic log only senses porosity between the interparticle, the presence of a percentage of the vuggy porosity may lead to inaccurate results. Where the permeability is affected by the size, distribution, and interconnection of pores more than by the total porosity values of the rock. Therefore, the current research is suggested to evaluate the permeability the use of the effective porosity that calculated from the neutron and density logs instead of the primary porosity (interparticles) that calculated from the sonic log. It appears from comparing the results for both permeability curves (i.e. that was calculated from the primary and effective porosities) that there is a clear contrast in the limestone rocks of Kurra Chine Formation, especially those rich with vuggy porosity. The reason for this is that many of these pores are connected to each other by micro-channels that was formed by dolomitization of the surrounding matrix as in Butmah well or as a result of recrystallization as in Ain Zalah and Alan wells. While the dolomitic rocks have convergent permeability values because the intercrystalline porosity are the basic pores in these rocks.